Descriptive study of cooperative language in primary care consultations by male and female doctors - Skelton, J R (British Medical Journal, 1999)
OBJECTIVE: To compare the use of some of the characteristics of male and female language by male and female primary care practitioners during consultations. DESIGN: Doctors’ use of the language of dominance and support was explored by using concordancing software. Three areas were examined: mean number of words per consultation; relative frequency of question tags; and use of mitigated directives. The analysis of language associated with cooperative talk examines relevant words or phrases and their immediate context. SUBJECTS: 26 male and 14 female doctors in general practice, in a total of 373 consecutive consultations. SETTING: West Midlands. RESULTS: Doctors spoke significantly more words than patients, but the number of words spoken by male and female doctors did not differ significantly. Question tags were used far more frequently by doctors (P<0.001) than by patients or companions. Frequency of use was similar in male and female doctors, and the speech styles in consultation were similar. CONCLUSIONS: These data show that male and female doctors use a speech style which is not gender specific, contrary to findings elsewhere; doctors consulted in an overtly non-directive, negotiated style, which is realised through suggestions and affective comments. This mode of communication is the core teaching of communication skills courses. These results suggest that men have more to learn to achieve competence as professional communicators.